Finnish Legislation on Land-Use Restrictions and Compensation - Katri Nuuja; Kauko Viitanen (Washington University Global Studies Law Review, 2007)
The aim of this Article is to present an overview on Finnish legislation on land-use restrictions and requirements for compensation in cases of different types of restrictions.
Keywords: Regulatory takings; Just compensation (Eminent domain); Land use controls; Property rights; Finland